Antigen-Specific TCR Signatures of Cytomegalovirus Infection - Huth, Alina; Liang, Xiaoling; Krebs, Stefan; Blum, Helmut; Moosmann, Andreas (The Journal of immunology (1950), 2019)
CMV is a prevalent human pathogen. The virus cannot be eliminated from the body, but is kept in check by CMV-specific T cells. Patients with an insufficient T cell response, such as transplant recipients, are at high risk of developing CMV disease. However, the CMV-specific T cell repertoire is complex, and it is not yet clear which T cells protect best against virus reactivation and disease. In this study, we present a highly resolved characterization of CMV-specific human CD8+ T cells based on enrichment by specific peptide stimulation and mRNA sequencing of their TCR β-chains (TCRβ). Our analysis included recently identified T cell epitopes restricted through HLA-C, whose presentation is resistant to viral immunomodulation, and well-studied HLA-B–restricted epitopes. In eight healthy virus carriers, we identified a total of 1052 CMV-specific TCRβ sequences. HLA-C–restricted, CMV-specific TCRβ clonotypes dominated the ex vivo T cell response and contributed the highest-frequency clonotype of the entire repertoire in two of eight donors. We analyzed sharing and similarity of CMV-specific TCRβ sequences and identified 63 public or related sequences belonging to 17 public TCRβ families. In our cohort, and in an independent cohort of 352 donors, the cumulative frequency of these public TCRβ family members was a highly discriminatory indicator of carrying both CMV infection and the relevant HLA type. Based on these findings, we propose CMV-specific TCRβ signatures as a biomarker for an antiviral T cell response to identify patients in need of treatment and to guide future development of immunotherapy.